2006
DOI: 10.1080/00016480500452525
|View full text |Cite
|
Sign up to set email alerts
|

Spiral ligament fibrocytes release chemokines in response to otitis media pathogens

Abstract: Protein array analysis showed that in response to NTHi or S. pneumoniae, rat SLFs released monocyte chemotactic protein 1, macrophage inflammatory protein 3 alpha, TNF-alpha, and cytokine-induced neutrophil chemoattractant 2 and 3. Treatment with IL-1alpha, on the other hand, resulted in release of MCP-1 but not the other molecules. Tissue inhibitor of metalloproteinase 1 and vascular endothelial growth factor were released regardless of the inflammatory stimulus used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 27 publications
2
53
1
1
Order By: Relevance
“…Our preliminary data showed that mononuclear cells infiltrated in the spiral ligament of the human cochlea with labyrinthitis, combined with OM, which is consistent with our hypothesis (data not shown). We also previously reported that the SLF cell line up-regulates various chemokines and cytokines upon exposure to lysate of NTHI, a common OM pathogen (72). NTHI-treated group (Fig.…”
Section: Nthi Highly Induces Mcp-1 In Slfssupporting
confidence: 61%
See 3 more Smart Citations
“…Our preliminary data showed that mononuclear cells infiltrated in the spiral ligament of the human cochlea with labyrinthitis, combined with OM, which is consistent with our hypothesis (data not shown). We also previously reported that the SLF cell line up-regulates various chemokines and cytokines upon exposure to lysate of NTHI, a common OM pathogen (72). NTHI-treated group (Fig.…”
Section: Nthi Highly Induces Mcp-1 In Slfssupporting
confidence: 61%
“…A solid-phase, sandwich-enzyme-linked immunosorbent assay (ELISA)-format, multiplexed protein assay was performed to simultaneously detect various cytokines released by activated cells (72). Briefly, the culture medium of SLFs was collected 48 h after treatment with either NTHI or PBS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cochlear inflammation is supposed to disrupt fibrocyte function of the spiral ligament; the stimulated fibrocytes produce chemoattractant mediators that induce prolonged inflammation and consequently lead to structural 366 T.N. ROTH changes, as mentioned above Moon et al, 2006). The reduced endocochlear potential not only affects the sensory part of the inner ear but also leads to alteration of the supporting structures, e.g., fibrocytes and connective tissue.…”
Section: Endocochlear Potentialmentioning
confidence: 99%